Oblique projection for direction‐of‐arrival estimation of hybrid completely polarised and partially polarised signals with arbitrary polarimetric array configuration. Issue 8 (1st October 2017) - Hou, Huijun; Mao, Xingpeng; Liu, Yongtan
Abstract : This study deals with the direction‐of‐arrival (DOA) estimation problem for hybrid completely polarised (CP) and partially polarised (PP) source signals using arbitrary polarimetric antenna arrays. An oblique projection‐based polarisation insensitive direction estimation (OPPIDE) algorithm is proposed by exploiting the spatial‐sparsity property of the sources. The OP technique is utilised to provide spatial filters, which are insensitive to the state of polarisation of signals, so that the potential source signals in the spatial domain can be separated later. The DOA estimation is finally implemented by identifying the sources' spatially sparse structure with the separated signals. Theoretical analysis indicates that the OPPIDE is applicable to any hybrid CP and PP signals, and is independent of special polarimetric array configurations. The effectiveness and superiority of the proposed OPPIDE are substantiated through making performance comparison with the present counterpart algorithms.